The mechanism of a PVDF/CsPbBr3 perovskite composite fiber as a self-polarization piezoelectric nanogenerator with ultra-high output voltage. Issue 41 (10th August 2022) - Xue, You; Yang, Tao; Zheng, Yapeng; Wang, Enhui; Wang, Hongyang; Zhu, Laipan; Du, Zhentao; Hou, Xinmei; Chou, Kuo-Chih
Abstract : The piezoelectric properties of conventional piezoelectric materials are generally obtained through the rearrangement of dipoles by an electric poling process. Abstract : The piezoelectric properties of conventional piezoelectric materials are generally obtained through the rearrangement of dipoles by an electric poling process. However, the piezoelectric properties show significant attenuation after the removal of the external electric field due to the depolarization effect. Therefore, the self-polarization effect with more stable piezoelectric properties has become a research focus. In this study, the dipole is rearranged by the aggregated charge at the interface of PVDF and CsPbBr3 . A PVDF/CsPbBr3 composite fiber with a high electroactive β phase content (94.6%) is prepared by an electrospinning method. The PVDF/CsPbBr3 piezoelectric nanogenerator (PENG) exhibits an outstanding voltage output ( V oc = 33 V) under self-polarization conditions, which is 6.6 times greater than that of the PVDF/perovskite composite counterpart previously recorded. Furthermore, the mechanism of self-polarization is revealed by analyzing the interfacial charge and electric field. Free electrons migrate and aggregate at the interface, giving the composite a built-in electric field, which leads to dipole self-polarization. Moreover, the practical applicability of PVDF/CsPbBr3 -PENG is studied by harvesting energy from human finger taps and successfully lighting up 120 LEDs and an electronic watch. Finally, the water, thermal, and continuous operating stability of the devices are tested to provide a reference for solving the instability problem of perovskites.